Reversing Cholinergic Bronchoconstriction by Common Inotropic Agents: A Randomized Experimental Trial on Isolated Perfused Rat Lungs. (September 2019) - Fodor, Gergely H.; Bayat, Sam; Babik, Barna; Habre, Walid; Peták, Ferenc
Abstract : BACKGROUND: The ability of inotropic agents to alter airway reactivity and lung tissue mechanics has not been compared in a well-controlled experimental model. Therefore, we compared the potential to alter lung tissue viscoelasticity and bronchodilator effects of commonly used inotropic agents in an isolated perfused rat lung model. METHODS: After achieving steady state lung perfusion, sustained bronchoconstriction was induced by acetylcholine (ACh). Isolated rat lungs were then randomly allocated to 6 groups treated with either saline vehicle (n = 8) or incremental concentrations of inotropes (adrenaline, n = 8; dopamine, n = 7; dobutamine, n = 7; milrinone, n = 8; or levosimendan, n = 6) added to the whole-blood perfusate. Airway resistance (Raw), lung tissue damping (G), and elastance were measured under baseline conditions, during steady-state ACh-induced constriction and for each inotrope dose. RESULTS: No change in Raw was observed after addition of the saline vehicle. Raw was significantly lower after addition of dopamine (maximum difference [95% CI] of 29 [12–46]% relative to the saline control, P = .004), levosimendan (58 [39–77]%, P < .001), and adrenaline (37 [21–53]%, P < .001), whereas no significant differences were observed at any dose of milrinone (5 [−12 to 22]%) and dobutamine (4 [−13 to 21]%). Lung tissue damping (G) was lower in animals receiving the highest doses of adrenaline (difference: 22 [7–37]%, P = .015), dobutamine (20 [5–35]%, P = .024), milrinone (20 [6–34]%, P = .026), and levosimendan (36 [19–53]%, P < .001) than in controls. CONCLUSIONS: Although dobutamine and milrinone did not reduce cholinergic bronchoconstriction, they reversed the ACh-induced elevations in lung tissue resistance. In contrast, adrenaline, dopamine, and levosimendan exhibited both potent bronchodilatory action against ACh and diminished lung tissue damping. Further work is needed to determine whether these effects are clinically relevant in humans.